INFORMATION SYSTEM FOR UTILIZATION OF SAGO PLANT (Metroxylon sagu) AS LOCAL FOOD IN LUWU DISTRICT WEB-BASED: SISTEM INFORMASI PEMANFAATAN TANAMAN SAGU(Metroxylon sagu) SEBAGAI PANGAN LOKAL DI KABUPATEN LUWUBERBASIS WEB - Nurul Qisti; Deril Alfiance Kaligi (PT. ROCE WISDOM ACEH, 2025)
LLuwu District is famous for its local food, namely sago (Metroxylon sago). The Local people process sago into special foods, such as kapurung, bagea, sinole, dange, etc. Not only does sago starch have benefits, but other components of the sago plant. Such as stems, leaves, roots, and midribs. So, information on the use of all components of the sago plant is needed so that it can be used as education for the public, especially in the Luwu district. The information system that will be designed is web-based and contains parts of the sago plant and its uses. The research design used in the website creation process is the Personal Home Page (PHP) Programming Language. The method used in this research design is the Structure Design Method and the test method uses the blackbox method and literature review. The research results obtained are in the form of a web-based educational application that can be accessed online by the wider community, especially people in Luwu District.